Robotic-Assisted Gait Training Combined with Multimodal Rehabilitation for Functional Recovery in Acute Dermatomyositis: A Case Report - Wilmer Esparza; Rebeca Benalcazar-Aguilar; Gabriela Moreno-Andrade; Israel Vinueza-Fernández (Brain Sciences)
This case report examines the impact of robotic-assisted therapy (Lokomat) on functional recovery in a 28-year-old male patient with acute dermatomyositis (DM), an autoimmune inflammatory myopathy causing progressive muscle weakness and disability. The patient underwent 21 sessions of robotic therapy combined with physical therapy, and occupational therapy over seven weeks. Assessments were conducted at baseline, week 10, and week 21 using standardized measures for balance, muscle strength, and functionality. Results demonstrated significant improvements across all domains: balance scores progressed from severe impairment (4/56 Berg, 0/28 Tinetti) to near-normal function (55/56, 24/28, respectively); muscle strength increased from grade 1/5 to 4/5 (MMT-8) in all tested muscle groups; and functionality improved from moderate dependence (59/126 FIM) to complete independence (126/126). The trunk functionality scores showed remarkable recovery from 12/100 to 100/100 (TCT), indicating restored trunk control. Lokomat-assisted therapy combined with conventional rehabilitation effectively improves proximal weakness and postural instability in DM. Robotic therapy enhances motor learning via repetitive movements and reduces therapist workload. Though limited by a single-case design, this study offers preliminary evidence for robotic rehabilitation in DM, previously unexplored. Controlled studies are needed to standardize protocols and validate results in larger cohorts. Advanced technologies show promise for functional recovery in inflammatory myopathies.